The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fphar.2021.718800
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Between Hyperprolactinemia, Metabolic Disturbance, and Sexual Dysfunction in Patients With Schizophrenia Under Olanzapine Treatment

Abstract: The aim of the study was to assess the relationship between prolactin levels and sexual dysfunction in patients with schizophrenia who use olanzapine medication. The potential risk factors of hyperprolactinemia and sexual dysfunction were also investigated. Patients with schizophrenia undergoing olanzapine monotherapy were invited to participate in this cross-sectional study. The Arizona Sexual Experiences Scale (ASEX) and the Positive and Negative Syndrome Scale were used to evaluate subjective sexual dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Seventy-two studies published between 1979 and 2021 were included in the random-effects model . The flow diagram is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Seventy-two studies published between 1979 and 2021 were included in the random-effects model . The flow diagram is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…64 Hyperprolactinaemia and secondary hypogonadism cause side-effects such as hirsutism, painful breast tension, sexual dysfunction, polycystic ovary syndrome, and osteoporosis, and increase the risk of breast cancer. [72][73][74] This increased risk is especially worrisome because genetic similarities have been shown between breast cancer and schizo phrenia phenotypes, 75 and women with SSD are less inclined to visit breast cancer screening facilities and less often follow treatment guidelines, which results in increased mortality (odds ratio 1•55; 95% CI 1•32-1•82). 76 Taken together, the mental and somatic health of women with SSD can be improved substantially when hormonal dysregulation can be prevented.…”
Section: Iatrogenic Prolactin Increasesmentioning
confidence: 99%
“…Among the many atypical antipsychotics, risperidone is considered to have one of the most significant effects on elevating prolactin (PRL) levels in psychiatric patients, and the PRL- increasing pharmacological effects of olanzapine should not be underestimated ( 1 ). A study from the Chinese province of Taiwan found that olanzapine can cause high levels of PRL (up to 51.6%) ( 4 ). What’s more, risperidone and olanzapine are two of the top-ranked antipsychotic drugs in terms of prescription rates, according to reports of prescribing patterns for psychiatric patients from around the world, including China ( 5 8 ).…”
Section: Introductionmentioning
confidence: 99%